Evaluation of Pharmacy Internship Programs among Pharmacy Schools in Metro Manila, Philippines - Carrido, Darwin I.; Lorenzo, Carlo Augustin A.; Macaldo, Aizel Camille L.
Internship program is an integral part of pharmacy education. Its evaluation is necessary to continuously develop a comprehensive program that is based on the needs and changing role of the profession. This study aimed to evaluate the three pharmacy internship programs (Community, Hospital and Industrial) among Philippine Association of Colleges of Pharmacy (PACOP) accredited schools in Metro Manila, Philippines. The study utilized a descriptive, correlational research design, using self-administered survey questionnaire as method of data collection. The questionnaires were tailored for each type of pharmacy practice setting. A total of 735 students responded in the survey. Descriptive statistical analysis, Pearson's Correlation Coefficient, One-Way ANOVA and Independent Samples t-test were used to analyze the data using IBM SPSS Statistics version 21 software. Overall, the student respondents rated their internship experiences positively and perceived high level of satisfaction with how the programs were carried out. Pharmacy interns also perceived to have acquired additional knowledge, improved skills and developed attitude from all pharmacy intership programs. Intership activities, intership experiences and level of satisfaction were found to be significantly correlated with the learning outcomes of each interhsip program. Despite limitation of participation to internship activities and problems and barriers encountered, the students perceived that the pharmacy internship program was effective in attaining its learning outcomes.
Keywords: Education, Pharmacy